CEO Dualism and Corporate Value: A Digital Corporate Governance Perspective - Mikrad; Galuh Febrianto, Hendra; Eky Pambudi, Januar (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Research aims: The aim of this research isto test and analyze the influence of CEO dualism on digital governance, General Meeting of Shareholders (GMS) and Cash ETR. Then digital corporate governance, and Cash ETR influence firm value. Design/Methodology/Approach: This research uses a quantitative approach based on associative-causality. As for the data collection techniques used in this research, it is the study of libraries and documentation of secondary data. This study uses path analysis (Path Analysis). Research findings: The results of this study are CEO dualism giving positive and significant influence on digital corporate governance, GMS and Cash ETR. In addition, digital corporate governance and Cash RTR also give positive and meaningful influence to firm value. Theoretical contribution/ Originality: The research provides a theoretical contribution that in discussing agency theory and stewardship theory there is a gap where the interests of managers that are always different in the interest of stakeholders have a gap with the theory of stewardships that wants the existence of managers to take precedence on cohesion, partnership, empowerment and mutual trust. Practitioner/Policy implication: The policy implications obtained in this study are the importance of the government in elevating policies in particular that relate to taxes on companies that already involve management as well as digital transactions as planned by the OECD. Research limitation/Implication: The research has the limitation that companies that go public on the Indonesian stock exchange have not fully implemented digital governance and implemented GMS digitally, so not all consumer goods companies are listed as samples of research.